The Influence of Environmental, Social, and Governance (ESG) on Company Performance - Adanan Silaban (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This research aims to determine the effect of environmental, social, and governance (ESG) disclosure on company profitability, especially in infrastructure sector companies listed on the Indonesia Stock Exchange. The population used was 62 companies. The sampling technique used the Purposive Sampling method, so that a sample of 27 companies was obtained that met the research criteria. This study is a quantitative study with the type of data source being secondary data obtained from the company's financial statements and annual reports. The analysis method used is multiple linear regression using SPSS version 25 software. Data testing was carried out using descriptive statistical analysis, classical assumption tests, multiple regression analysis tests, coefficients of determination and t-tests. The independent variables used are environmental, social, and governance (ESG) while the dependent variable is profitability which is proxied by Return On Asset (ROA). The results of the study indicate that environmental, social, and governance (ESG) disclosure has a positive and significant effect on profitability. In addition, based on the determination coefficient test (R2), environmental, social, and governance are able to explain their effect on profitability by 74.2% of the dependent variable. Based on the research results, it was concluded that ESG has a positive effect on company performance. Suggestions that can be given for further research are to add variables that are not included in this study that are considered to affect environmental, social and governance (ESG) disclosure and to increase the research period to obtain accurate results.